A Theory Of Good Governance Or Good Government - Lane, Jan-Erik (Advances in Social Sciences Research Journal, 2018)
The United Nations’ endorsed notion of good government or governance can be analysed in a clear fashion with the concepts of rule of law – rule of law I (legality) and rule of law II (democracy). Principal-agent modelling shows how politicians and the bureaucracy can be restrained by rule of law institutions.